Association of corticosteroid use and attention deficit/hyperactivity disorder in asthmatic children varies by age. (3rd April 2023) - Xie, Luyu; Gelfand, Andrew; Mathew, M. Sunil; Atem, Folefac D.; Delclos, George L.; Messiah, Sarah E.
Abstract: Objective: We aim to examine the impact of corticosteroids use on ADHD among children with asthma by administration routes. Methods: A population-based, cross-sectional analysis included pediatric patients ages 5–20 years old from the 2016 and 2019 Kids Inpatient Database (unweighted N  = 111, 702). ICD-10-CM codes were used to identify corticosteroids use, asthma, and ADHD cases. Survey logistic regression models with purposeful variable selection algorithms were built to examine the association between corticosteroids use, and ADHD by asthma severity and age. An inverse probability weighting (IPW) approach was used to help further control residual confounding, Results: Among children aged 5–11 years old, the odds of ADHD were significantly higher in children with moderate to severe asthma who used inhaled corticosteroids than nonusers (moderate asthma: adjusted odds ratios [aOR] 1.46, 95% confidence interval [CI] 1.14–2.44; severe asthma: aOR 1.61, 95% CI 1.18–2.21). Although oral corticosteroid use was not independently associated with ADHD in young children, combined use of inhaled and oral corticosteroid had almost 5 times higher odds of use among ADHD in children with severe asthma vs. nonusers (aOR 4.85, 95% CI 2.07 − 11.35). No associations were found between any corticosteroid use and ADHD among asthmatic children aged 12–20 years. Conclusions: In this retrospective analysis, we found inhaled corticosteroids were positively associated with ADHD in younger children with moderate to severe asthma, but not in older children.